Performance comparison of encryption IPsec VPN encryption techniques / Nur Hasyimah Mohd Ridzuan and Ruhani Ab Rahman - Mohd Ridzuan, Nur Hasyimah; Ab Rahman, Ruhani
Internet Protocol Security (IPSEC) is one of the protocol implements in VPN site to site tunnels network. Where Virtual Private network (VPN) is a technology that used to transmit information via insecure regions such as internet from one office on one geographical area to another geographical area. IPSEC protocol network setup encrypt the overall IP traffic packets before being transferred from source to destination in order to secure the tunnels. This paper presents the implementation of site to site VPN tunneling using a network simulator. By varying the combination of encryption algorithm 3DES and AES 256 with two hashing type SHA-1 and MD5, the performance of each algorithm was compared and analyzed via Window 7 environment. The implementation of IPSEC protocol via Cisco equipments was introduced. Results indicate different algorithms (with and without encryption), hashing method and packet length have influence on Round Trip Time (RTT).